2010
DOI: 10.2139/ssrn.1573872
|View full text |Cite
|
Sign up to set email alerts
|

Microfinance and Gender: Is There a Glass Ceiling in Loan Size?

Abstract: Microfinance institutions serve a majority of female borrowers. But do men and women benefit from same credit conditions? This paper investigates this issue by presenting an original model and testing its predictions on an exceptional database including 34,000 loan applications from a Brazilian microfinance institution over an eleven-year period. The model considers a lender that offers standardized loan contracts with a fixed interest rate, which is common practice in microfinance. It demonstrates that biased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
64
1
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(77 citation statements)
references
References 34 publications
10
64
1
2
Order By: Relevance
“…This confirms previous evidence on Brazilian microfinance (Agier and Szafarz, 2013a). Regarding the interplay of gender concern and regulation change, our findings are the following.…”
Section: Columns (3) and (4) Insupporting
confidence: 91%
See 2 more Smart Citations
“…This confirms previous evidence on Brazilian microfinance (Agier and Szafarz, 2013a). Regarding the interplay of gender concern and regulation change, our findings are the following.…”
Section: Columns (3) and (4) Insupporting
confidence: 91%
“…Table 2 shows that the sizes of the loans granted by the MFI to women exhibit similar features. This gender-specific credit rationing is in line with previous evidence by Agier and Szafarz (2013a), who detect a "glass-ceiling effect" at a Brazilian MFI, meaning that loan approval is not discriminatory but that women with ambitious projects tend to receive smaller loans than men. Presumably, the fact that gender-related disparate treatment in microcredit affects credit conditions rather than loan approval is linked to the microfinance tradition of serving female borrowers (Armendariz and Morduch, 2010).…”
Section: By Imposing a Low Loan Ceiling On Mfis The French Conseil Dsupporting
confidence: 90%
See 1 more Smart Citation
“…Women are kept being more credit-constrained than men by MFIs (Berger, 1990;Fletschner, 2009). Built on a unique database from Brazilian microfinance institution over an eleven-year period, Agier and Szafarz (2013) detected no discriminatory practice in the approval rate, but uncovered a gender gap in loan size. They concluded that glass ceiling effect was greater for female borrowers than for male borrowers.…”
Section: Literature Backgroundmentioning
confidence: 98%
“…Moreover, due to a lack of data, studies of discrimination in developing countries are even more scarce (Agier & Szafarz, 2013). Fortunately, the presence of online peer-to-peer lending provides a unique opportunity to empirically examine and understand this phenomenon in developing countries.…”
Section: Literature Backgroundmentioning
confidence: 99%